Terson’s syndrome: An interesting case report - Rajwinder Kaur; Mehak Mangla; Balbir Khan; Harleen Kaur (Journal of Clinical Ophthalmology and Research)
Terson’s syndrome is described as an intra-ocular hemorrhage (sub hyaloid, intraretinal, subretinal bleed, or vitreous) occurring secondary to raised intracranial pressure (ICP) secondary to any intra cranial hemorrhage or traumatic brain injury. This report presents a case of a 34-year-old male who was diagnosed with a ruptured aneurysm of the left middle cerebral artery, which led to intracranial hemorrhage followed by raised ICP. On recovery, he noticed the loss of vision in both eyes. After 2 months, he was brought to an ophthalmologist in wheelchair for further detailed evaluation, where he was diagnosed with bilateral dense vitreous hemorrhage, making him blind (hand movements positive [HM+]) for 2 months. In view of bilateral involvement and HM+ in both eyes, 23G pars plana vitrectomy was performed in both eyes. Hence, a high index of suspicion and early intervention in cases of bilateral dense vitreous hemorrhage can result in a favorable visual outcome (visual acuity of 20/30 in both eyes).